2020
DOI: 10.1128/aem.02825-19
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Profiling of the Dental Mycobiome Reveals Strong Taxonomic Shifts during Progression of Early-Childhood Caries

Abstract: Dental caries is one of the most common diseases worldwide. Bacteria and fungi are both commensals in the oral cavity; however, most research regarding caries has focused on bacterial impacts. The oral fungal mycobiome associated with caries is not well characterized, and its role in disease is unclear. ITS1 amplicon sequencing was used to generate taxonomic profiles from site-specific supragingival plaque samples (n = 82) obtained from 33 children with different caries status. Children were either caries free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
58
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 80 publications
7
58
1
Order By: Relevance
“…The role of the oral mycobiome in caries has been the focus of recent research. Several mycobiome studies have explored fungal community diversity in relation to caries in children (Fechney et al 2019; Baraniya et al 2020; de Jesus et al 2020; O’Connell et al 2020). Studies that compared the oral mycobiome between caries-free and caries-affected children with mixed dentition reported differences in abundance of certain fungi according to caries status.…”
Section: Role Of the Oral Mycobiome In Dental Cariesmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of the oral mycobiome in caries has been the focus of recent research. Several mycobiome studies have explored fungal community diversity in relation to caries in children (Fechney et al 2019; Baraniya et al 2020; de Jesus et al 2020; O’Connell et al 2020). Studies that compared the oral mycobiome between caries-free and caries-affected children with mixed dentition reported differences in abundance of certain fungi according to caries status.…”
Section: Role Of the Oral Mycobiome In Dental Cariesmentioning
confidence: 99%
“…This study also reported differences in the mycobiome and its relationship to caries according to sex, with caries-free females showing an enrichment of Malassezia restricta . In a site-specific analysis of the mycobiome associated with ECC, caries-free children were compared to those with lesions in enamel or dentin, also discriminating between healthy surfaces, sites with enamel caries, and dentin lesions (O’Connell et al 2020). This study showed a trend for decreased mycobiome diversity as caries severity increased and found C. albicans and C. dubliniensis were positively correlated with caries.…”
Section: Role Of the Oral Mycobiome In Dental Cariesmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have reported that C. albicans can often be detected with S. mutans in ECC dental plaque samples, and the detection rate of C. albicans is significantly higher in children with ECC than in caries-free children ( Yang et al, 2012 ; Xiao et al, 2018a , b ). High-throughput amplicon sequencing was used to characterize the oral microbiome associated with ECC, and the results indicated that C. albicans was the most abundant fungus and correlated with caries ( O’Connell et al, 2020 ). Therefore, C. albicans , as a part of dental plaque, can enhance the virulence of plaque biofilms and is considered to be an important factor in ECC ( Hajishengallis et al, 2017 ; Koo et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fluoride prophylaxis in the form of toothpastes, mouth rinses, professional fluoride treatment, and dental cavity filling with fluoride-releasing materials is a widely used strategy to prevent caries. However, due to the large role of dietary factors in its pathogenesis, it is important to replace sucrose-rich foods with foods lacking simple sugars or with natural sucrose substitutes such as xylitol, sorbitol, or erythritol, additionally characterized by cariostatic properties [16,21].…”
Section: Introductionmentioning
confidence: 99%